Intraperitoneal administration of thermosensitive hydrogel Co-loaded with norcantharidin nanoparticles and oxaliplatin inhibits malignant ascites of hepatocellular carcinoma - Susu Xiao; Yu Wang; Wenqiong Ma; Ping Zhou; Biqiong Wang; Zhouxue Wu; Qian Wen; Kang Xiong; Yanlin Liu; Shaozhi Fu (Taylor & Francis Group, 2022)
Malignant ascites is a common complication of some advanced cancers. Although intraperitoneal (IP) administration of chemotherapy drugs is routinely used to treat cancerous ascites, conventional drugs have poor retention and therefore need to be administered frequently to maintain a sustained anti-tumor effect. In this study, a thermosensitive hydrogel composite loaded with norethindrone nanoparticles (NPs) and oxaliplatin (N/O/Hydrogel) was developed to inhibit ascites of hepatocellular carcinoma (HCC) through IP injection. N/O/Hydrogel induced apoptosis in the H22 cells in vitro, and significantly inhibited ascites formation, tumor cell proliferation and micro-angiogenesis in a mouse model of advanced HCC with ascites, and prolonged the survival of tumor-bearing mice. Histological examination of the major organs indicated that the hydrogel system is safe. Taken together, the N/O/Hydrogel system is a promising platform for in-situ chemotherapy of malignant ascites.